Study of Gust Calculation and Gust Alleviation: Simulations and Wind Tunnel Tests - Yitao Zhou; Zhigang Wu; Chao Yang (Aerospace, 2023)
Feedforward gust alleviation control using gusts as input signals has received increasing attention in recent years. One of the most important issues in such a control scheme is how to obtain the high-quality gust information during an aircraft’s flight. In this study, a calculation method for obtaining gust information when an aircraft is flying with an arbitrary attitude is derived, based on which a simplified calculation method is established. A wind tunnel test was carried out to verify the gust calculation method. Numerical simulations were employed to investigate the influence of sensor characteristics on the gust calculation accuracy and gust alleviation performance. The results show that the time delay of the sensor has a very important influence and leads to decreases in the gust calculation accuracy and the alleviation effect. A five-hole probe was mounted on an aircraft model for gust sensing, and a gust alleviation wind tunnel test was conducted by combining the gust calculation with the feedforward gust alleviation system. The accurate calculation of the gust signal enables the feedforward gust alleviation system to achieve a 39.12% reduction of wing root bending moment and a 65.47% reduction of wingtip acceleration on average.